Intestinal Parasites of Neotropical Wild Jaguars, Pumas, Ocelots, and Jaguarundis in Colombia: Old Friends Brought Back from Oblivion and New Insights - Uribe, Manuel; Payán, Esteban; Brabec, Jan; Vélez, Juan; Taubert, Anja; Chaparro-Gutiérrez, Jenny J; Hermosilla, Carlos (Pathogens (Basel, Switzerland), 2021)
Neotropical wild felids (NWF) are obligate carnivore species present in Central and South America, and some are considered endangered due to constantly decreasing populations. NWF can become infected by a wide range of protozoan and metazoan parasites, some of them affecting their health conditions and others having anthropozoonotic relevance. Parasitological studies on NWF are still very scarce, and most data originated from dead or captive animals. On this account, the current study aimed to characterize gastrointestinal parasites of free-ranging jaguars (Panthera onca), pumas (Puma concolor), ocelots (Leopardus pardalis), and jaguarundis (Herpailurus yagouaroundi), i.e., four out of six NWF species endemic to Colombia. Fecal samples from jaguars (n = 10) and ocelots (n = 4) were collected between 2012 and 2017 as part of the Jaguar Corridor Initiative from six geographic locations in Colombia. In addition, cestode specimens were obtained during puma and jaguarundi necropsies. Scat samples were processed by standardized sodium acetate-acetic acid-formalin (SAF), sedimentation, and flotation techniques and by carbol fuchsin-stained fecal smears. Morphological evaluation of feces showed the presence of one cestode (Spirometra sp.), a nematode (Toxocara cati), an acanthocephalan (Oncicola sp.), and one cyst-forming coccidian (Cystoisospora-like oocysts). Feces oocysts were submitted to a Toxoplasma gondii-specific PCR for species identification, but no product was amplified. The cestodes isolated from a puma and jaguarundi were molecularly characterized by sequencing cytochrome c oxidase subunit I, identifying them as Taenia omissa and as a T. omissa sister lineage, respectively. These results collectively demonstrate the potential role of NWF as natural reservoir hosts for neglected zoonotic parasites (e.g., Spirometra sp., T. cati) and highlight their possible role in parasite transmission to human communities. Due to public health concerns, the occurrence of these parasites should be monitored in the future for appropriate zoonotic management practices in conservation strategies and wild felid health management programs.
Keywords: Spirometra sp.; Oncicola sp.; ocelot; jaguar; puma; Taenia omissa; jaguarundi; Cystoisospora sp.; Toxocara cati